The chain mediating role of social support and yielding coping style between health literacy and symptom burden in patients with chronic heart failure - Yan, Jing; Zhou, Long; Song, Guangyu; Yuan, Yangyang (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo explore the mediating effects of social support and coping style on health literacy and symptom burden in patients with chronic heart failure.MethodsA total of 200 patients with chronic heart failure in Grade 3A Hospitals in Jiangsu province of China were investigated by using General Data Questionnaire, Memorial Symptom Assessment Scale for Heart Failure, Chinese Version of Heart Failure Specific Health Literacy Scale, Perceived Social Support Scale, and Medical Coping Modes Questionnaire.ResultsSymptom burden score of patients with chronic heart failure was (0.73 ± 0.45), health literacy score was (29.38 ± 9.76), social support score was (59.15 ± 10.58), and yielding coping style score was (9.18 ± 4.13). There were significant correlations among health literacy, social support, coping style and symptom burden in patients with chronic heart failure. The results of mediating effect analysis showed that health literacy of patients with chronic heart failure could influence symptom burden through the chain mediating effect of social support—yielding coping style. The effect size was −0.008, and the 95% confidence interval did not include 0 (−0.011, −0.006).ConclusionThe health literacy of patients with chronic heart failure has an indirect impact on the burden of symptoms through social support and yielding coping style, suggesting that medical staff should take social support and coping style as a breakthrough from the perspective of health literacy of patients with chronic heart failure, so as to achieve the purpose of improving the health literacy of patients with chronic heart failure and reducing the burden of symptoms.